1998
DOI: 10.1046/j.1365-2095.1998.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a spray-dried artificial diet for larval culture of freshwater prawn, Macrobrachium rosenbergii , and striped bass, Morone saxatilis

Abstract: Larvae of the freshwater prawn, Macrobrachium rosenbergii (De Man), and the striped bass, Morone saxatilis (Walbaum), were fed artificial diets manufactured by a spray‐drying process or live Artemia nauplii, separately or in various combinations. Spray‐dried diets were neutrally buoyant, water stable (low protein leaching rate), and were satisfactorily consumed as verified by the observation of full guts after feeding. Survival and growth of larvae fed live Artemia nauplii was significantly greater than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The lack of development in larvae that were fed the dry feed may be due to a lack of digestive enzymes, particularly pepsin, and a lack of GI development, as has been suggested by others (Dabrowski and Culver 1991;Ohs 1995;Langdon and Barrows 2011). In addition, I hypothesize that the lack of development in the hybrid striped bass larvae may have been related to osmotic stress due to the ingestion of dry feed with a high osmotic load or (as expressed by Ohs et al 1998) a high density. In larvae that received the dry artificial diet, both the epidermal and gut epithelial cells exhibited osmotic stress, as indicated by the loss of microridge structure, dissociation of the RER, and eventual cell necrosis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The lack of development in larvae that were fed the dry feed may be due to a lack of digestive enzymes, particularly pepsin, and a lack of GI development, as has been suggested by others (Dabrowski and Culver 1991;Ohs 1995;Langdon and Barrows 2011). In addition, I hypothesize that the lack of development in the hybrid striped bass larvae may have been related to osmotic stress due to the ingestion of dry feed with a high osmotic load or (as expressed by Ohs et al 1998) a high density. In larvae that received the dry artificial diet, both the epidermal and gut epithelial cells exhibited osmotic stress, as indicated by the loss of microridge structure, dissociation of the RER, and eventual cell necrosis.…”
Section: Discussionmentioning
confidence: 85%
“…Striped bass and hybrids have a short yolk sac period, with larval stages that possess a very rudimentary digestive tract (i.e., lacking a functional stomach or gastric glands) and that must undergo complex metamorphosis of the digestive system to survive. Ohs et al (1998) and Ohs (1995) suggested that the poor survival of striped bass and white bass Morone chrysops × striped bass hybrids (hereafter, hybrid striped bass) that were offered even sophisticated artificial diets was due to rapid gut evacuation or a lack of appropriate digestive enzyme activity (or both) in the premetamorphic larvae. Digestive enzymes are known to be active in larval striped bass from the time of hatch (Baragi and Lovell 1986); the notable exception is pepsin, which is not produced until the gastric glands of the stomach become differentiated.…”
mentioning
confidence: 99%
“…Notably, survival from newly hatched phyllosoma to puerulus under these feeding regimes is typically very low, and hence unviable from a commercial perspective . The development of formulated feeds for larval crustaceans presents many advantages including nutrient optimisation, consistent quality, and generally, a lower cost (Andres et al, 2011;Kovalenko et al, 2002;Ohs et al, 1998). However, poor digestibility and subsequent difficulties in nutrient assimilation are often present as crucial obstacles in the successful replacement of live feeds with formulated feeds (Arredondo-Figueroa et al, 2013;Cahu et al, 1999;Jones et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulated diet (MD) use has become highly successful in conventional shrimp larviculture because it eliminates the need for costly and labor-intensive culture of live food, are available throughout the year, are conveniently stored, are easy to use, and their nutrient composition is easily modified (Ohs et al 1998). The search for simpler technological processes and new ingredients that adjust to the available local resources and economics, particularly in developing countries, represents an ongoing effort.…”
mentioning
confidence: 99%
“…WPC seems to possess many of the characteristics desired for a microencapsulating agent ) and possesses a high concentration of good quality protein, is low in lipid, ash, and indigestible fiber, resulting in high digestibility (Morr and Foegeding 1990;de Wit 1998), which provides them with a potential dual functionality as an encapsulating agent and protein source in diets. The use of terrestrial animal protein sources (sodium caseinate, meat, animal plasma protein, pork liver, albumin, or protein from poultry by-products) in aquaculture diets has been previously studied (Ohs et al 1998;Yufera et al 1999;Davies and Arnold 2000).…”
mentioning
confidence: 99%